2001
DOI: 10.1542/peds.107.3.e41
|View full text |Cite
|
Sign up to set email alerts
|

Is Breastfeeding Really Favoring Early Neonatal Jaundice?

Abstract: ABSTRACT. Objective. The purpose of this study was to evaluate the development of significant hyperbilirubinemia in a large unselected newborn population in a metropolitan area with particular attention to the relationship between type of feeding and incidence of neonatal jaundice in the first week of life.Study Design. A population of 2174 infants with gestational age >37 weeks was prospectively investigated during the first days of life. Total serum bilirubin determinations were performed on infants with jau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
2
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 23 publications
7
63
2
8
Order By: Relevance
“…Decreased caloric intake, inhibition of hepatic excretion of bilirubin, and an increase in intestinal absorption of bilirubin (enterohepatic circulation) are suggested mechanisms for early neonatal hyperbilirubinaemia associated with breastfeeding (24). Recently, a large population study showed the important role of fasting, but not breastfeeding per se, in the pathogenesis of neonatal hyperbilirubinemia (26). In addition, Ishihara et al (27) demonstrated that mutation in the TATA box or in the coding region of UGT1A1 was found to have significantly higher increment of serum bilirubin values in healthy adult subjects than individuals without any mutation after caloric restriction.…”
mentioning
confidence: 99%
“…Decreased caloric intake, inhibition of hepatic excretion of bilirubin, and an increase in intestinal absorption of bilirubin (enterohepatic circulation) are suggested mechanisms for early neonatal hyperbilirubinaemia associated with breastfeeding (24). Recently, a large population study showed the important role of fasting, but not breastfeeding per se, in the pathogenesis of neonatal hyperbilirubinemia (26). In addition, Ishihara et al (27) demonstrated that mutation in the TATA box or in the coding region of UGT1A1 was found to have significantly higher increment of serum bilirubin values in healthy adult subjects than individuals without any mutation after caloric restriction.…”
mentioning
confidence: 99%
“…Sezaryen ile doğanların yatış bilirubin düzeyi ortalaması 16,89±3,6, NSVY ile doğanlarınki 17,2±3,65 idi. Doğum şekline göre yatış bilirubin düzeyi benzer bulundu (p:0,48) beslenen bebeklerin bilirubin düzeyinin daha düşük olduğu gösterilmiştir (21). Tan ve ark'nın çalışmasında olguların %18,2'de patolojik tartı kaybı saptanırken, bizim çalışmamızda patolojik tartı kaybı oranı %6,4ʼidi (16).…”
Section: Discussionunclassified
“…Bertini ve ark. [19] 2174 yenidoğan ile yaptıkları çalışmada beslenme şekli, tartı kaybı, doğum şeklinin belirgin hiperbilirubinemi gelişmesine etkisini incelemişlerdir. Anne sütü alan bebeklerde ilk günlerde belirgin hiperbilirubinemiyi sık bulmamışlardır.…”
Section: Discussionunclassified